A Habermasian Critique of Student Representation in the University of the Philippines - Catacutan, Kaira Millen (Dúnong: UP Diliman Journal of Student Research; Vol 2 (2023), 2025)
This research is a manifestation and a statement on the unexamined and subpar state of student politics in the University of the Philippines Diliman (UP Diliman). Student politics, overhauled by student political parties, belongs in the Habermasian concept of the System. Student political parties are composed of students and alliance student organizations, which subscribe to a specific set of principles and ideologies when concerning nationalism, tackling social ills, and student governance. This paper explains how the conspicuous, unregulated politicking subverts student democracy—the core foundation of the student council as an institution.